(untitled) (Olhar de Professor, 2011)
The present article discusses some key aspects related to the praxis and theory of qualitative research, highlighting its potentials, limits and constructive criticism. The research results include reflections on the possibilities of using different qualitative research tools (diaries, questionnaires, semi-structured interviews, focus groups, participatory video, participant observation and the use of diagrams) to study different issues related to consumption. The research was focused on various aspects of consumption. Consumption is an issue of great relevance both in terms of environmental sustainability and to formal education despite the intense publicity that favor the use of the different medias.